Fear of liftoff: Uncertainty, rules and discreation in monetary policy normalization - Athanasios Orphanides (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
The Federal Reserve's muddled mandate to attain simultaneously the incompatible goals of maximum employment and price stability invites short-term-oriented discretionary policymaking inconsistent with the systematic approach needed for monetary policy to contribute best to the economy over time. Fear of liftoff-the reluctance to start the process of policy normalization after the end of a recession-serves as an example. Causes of the problem are discussed, drawing on public choice and cognitive psychology perspectives. The Federal Reserve could adopt a framework that relies on a simple policy rule subject to periodic reviews and adaptation. Replacing meeting-by-meeting discretion with a simple policy rule would eschew discretion in favor of systematic policy. Periodic review of the rule would allow the Federal Reserve the flexibility to account for and occasionally adapt to the evolving understanding of the economy. Congressional legislation could guide the Federal Reserve in this direction. However the Federal Reserve may be best placed to select the simple rule and could embrace this improvement on its own, within its current mandate, with the publication of a simple rule along the lines of its statement of longer-run goals.
urn:nbn:de:hebis:30:3-382909
Keywords: E32; E52; E58; E61; 330; Federal Reserve; liftoff; discretion; policy rules; policy normalization